2012
DOI: 10.1094/pdis-07-11-0571
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Communities Associated with Potato Common Scab-Suppressive Soil Determined by Pyrosequencing Analyses

Abstract: Potato common scab, caused by Streptomyces spp., is an annual production problem for potato growers, and not effectively controlled by current methods. A field with naturally occurring common scab suppression has been identified in Michigan, and confirmed to have a biological basis for this disease suppression. This field and an adjacent scab nursery conducive to disease were studied using pyrosequencing to compare the two microbial communities. Total DNA was extracted from both the disease-conducive and -supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
97
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(120 citation statements)
references
References 50 publications
12
97
4
Order By: Relevance
“…As others have found in community-based analyses of suppressive soils (Sanguin et al, 2009;Mendes et al, 2011;Rosenzweig et al, 2012), no single phylum was uniquely associated with disease suppression in the strawberry wilt microbiome (Table 1 and Supplementary Tables S4, S5 and S6). Instead, our identification of antibiotic-producing Streptomyces as participating in the suppression of Fusarium wilt also required culture-based approaches that have long implicated specific microorganisms in those instances where the etiology of specific soil suppressiveness has been at least partially resolved.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…As others have found in community-based analyses of suppressive soils (Sanguin et al, 2009;Mendes et al, 2011;Rosenzweig et al, 2012), no single phylum was uniquely associated with disease suppression in the strawberry wilt microbiome (Table 1 and Supplementary Tables S4, S5 and S6). Instead, our identification of antibiotic-producing Streptomyces as participating in the suppression of Fusarium wilt also required culture-based approaches that have long implicated specific microorganisms in those instances where the etiology of specific soil suppressiveness has been at least partially resolved.…”
Section: Discussionmentioning
confidence: 65%
“…have long been known to contribute to the suppression of common scab of potato caused by pathogenic Streptomyces spp. (Bowers et al, 1996;Lorang et al, 1989), community-based studies of such soils have shown that multiple taxa are associated with suppression but have not resolved functionally active agents at the species or subspecies level in either pathosystem (Sanguin et al, 2009;Rosenzweig et al, 2012). A third study, guided by a community-based approach and on which our work was modeled, also identified multiple phyla in a soil suppressive of damping-off disease caused by Rhizoctonia solani, but culturebased methods were needed to identify specific strains of an antibiotic-producing Pseudomonas inhibitory to the pathogen (Mendes et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…38) provide a very good 'model system'to unravel and design the optimal microbial consortium to protect plants from infection by soil-borne pathogens. Studies by Kyselkova et al (2009);Mendes et al (2011) and Rosenzweig et al (2012) on soils suppressive to different fungal and bacterial plant pathogens pinpointed multiple bacterial genera that were more abundant in the suppressive than in the corresponding disease conducive soils. Although the potential role of the identified bacterial communities in disease suppressiveness was addressed for only a few genera, these studies do provide a framework to reconstruct microbial consortia for disease control.…”
Section: Reconstructing a 'Minimal Rhizosphere Microbiome'mentioning
confidence: 98%
“…Previous studies have reported that there are usually more unique 245 OTUs in the rhizosphere of healthy soil than in diseased soil (Rosenzweig et al, 2012). In the 246 phyllosphere, there may be same phenomenon as the soil.…”
mentioning
confidence: 98%